Susceptibility of staphylococcus epidermidis planktonic cells and biofilms to the lytic action of staphylococcus bacteriophage K - Cerca, Nuno (2007)
Aims: To evaluate differences in biofilm or planktonic bacteria susceptibility to be killed by the polyvalent antistaphylococcus bacteriophage K. Methods and Results: In this study, the ability of phage K to infect and kill several clinical isolates of Staphylococcus epidermidis was tested. Strains were grown in suspension or as biofilms to compare the susceptibility of both phenotypes to the phage lytic action. Most strains (10/11) were susceptible to phage K, and phage K was also effective in reducing biofilm biomass after 24 h of challenging. Biofilm cells were killed at a lower rate than the log-phase planktonic bacteria but at similar rate as stationary phase planktonic bacteria. Conclusions: Staphylococcus epidermidis biofilms and stationary growth phase planktonic bacteria are more resistant to phage K lysis than the exponential phase planktonic bacteria. Significance of study: This study shows the differences in Staph. epidermidis susceptibility to be killed by bacteriophage K, when grown in biofilm or planktonic phenotypes.